Computational Notification of Relative Displacement Variations in Estimation of Seismic Demand of Mid-Rise Moment Frame Skeletons - Saman Khalili (Iranian Society of Structrual Engineering (ISSE), 2018)
Dynamic time history analysis methods are commonly used to determine the seismic responses of structures. Despite their ability to somewhat precisely estimate seismic demand, nonlinear dynamic methods require extensively complex computations and are sensitive to the nature of earthquake records. Nonlinear static analysis methods also estimate the seismic responses of structures within an error range. The continuum analytical model is an alternative computation method for estimation of the seismic demand of structures. If the seismic behaviour of a structure is modeled based on the interaction between the equivalent flexural and shear cantilevers, it is possible to develop an analytical procedure based on the closed-form equations. In this study, the studied models were prepared using a hybrid and a bundled moment framed tube skeletons as 10-story structures which are symmetric and regular with plan and height. The variations range of seismic responses of the studied structures was calculated using the closed-form model of flexural and shear combined cantilever. Then, these results are compared with the response parameters obtained from linear and nonlinear time history analyses subjected the three components earthquake records contain strong forward directivity effects. Some of the characteristics of near-field records are powerful low-frequency band, pulse-like motions with long periods, rapid release of kinetic vibration energy in a short period, and ratio of peak velocity to peak acceleration. This research results denote the presence of an overestimation on the seismic demand parameters with relative precision.